Synthesis of intermediates for carbapenem antibiotics and synthetic analogues of dehydroepiandrosterone (DHEA) - Burke, Catherine M. (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2000)
The work presented in this thesis is divided into two parts. Part one consists of the synthesis and chemical modification of β-lactams as potential intermediates for carbapenem antibiotics. Part two describes the synthesis of analogues of 3β-androst-5-ene-17-one (DHEA) and 3β-hydroxyandrost-5-ene-7,17-dione (7-oxo-DHEA) as potential therapeutic agents. The carbapenems are a group of non-classical β-lactam compounds containing a bicyclic carbapen-2-em-3-carboxylic acid nucleus. They possess potent antibacterial activity together with an unprecendented level of stability to a wide variety of β- lactamases. Thienamycin, the first known carbapenem was isolated from Streptomyces cattleya in 1976. The C-2 aminoethylthio substituent or a derivative thereof is accredited with the antipseudomonal activity demonstrated, while the hydroxyethyl or substituted alkyl C-6 substituent is thought to be responsible for the high degree of β-lactamase stability observed for these structures. Research to date involving the development of synthetic carbapenems has concentrated on the modification of the C-2 side chain. In this work the synthesis of monocyclic β- lactams containing a reactive C-3 vinyl side chain, which are suitably substituted to facilitate conversion to novel carbapenem compounds is presented.
Keywords: Pharmaceutical Chemistry, Ph.D.; Ph.D. Trinity College Dublin